On the economic risk capital of portfolio insurance - Werner Hürlimann (International Journal of Mathematics and Mathematical Sciences)
A formula for the conditional value-at-risk of classical portfolio insurance is derived and shown to be constant for sufficiently small loss probabilities. As illustrations, we discuss portfolio insurance for an equity market index using empirical data, and analyze the more general multivariate situation of a portfolio of risky assets.